2022
DOI: 10.3389/fcell.2022.834754
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy in Limb Ischemia: State-of-Art, Perspective, and Possible Impacts of Endometrial-Derived Stem Cells

Abstract: As an evidence-based performance, the rising incidence of various ischemic disorders has been observed across many nations. As a result, there is a growing need for the development of more effective regenerative approaches that could serve as main therapeutic strategies for the treatment of these diseases. From a cellular perspective, promoted complex inflammatory mechanisms, after inhibition of organ blood flow, can lead to cell death in all tissue types. In this case, using the stem cell technology provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 179 publications
1
4
0
Order By: Relevance
“…Earlier studies demonstrated that Nqo-1 counteracts intracellular ROS generation, thus attenuating DNA damage and improving cell survivability. [26,72] Our experimental results confirm for the first time that bile acid-FXR axis activation significantly improves the antiapoptotic effect of ADSC by promoting Nqo-1 expression, thus increasing the quantity of transplanted MSC.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Earlier studies demonstrated that Nqo-1 counteracts intracellular ROS generation, thus attenuating DNA damage and improving cell survivability. [26,72] Our experimental results confirm for the first time that bile acid-FXR axis activation significantly improves the antiapoptotic effect of ADSC by promoting Nqo-1 expression, thus increasing the quantity of transplanted MSC.…”
Section: Discussionsupporting
confidence: 66%
“…[ 70,71 ] However, as one of the key features in the myocardial ischemic microenvironment, excessive oxidative stress is directly harmful to ADSC survival. [ 26 ] Inconsistent with the in vivo results, cellular experiments failed to confirm that FXR overexpression promoted ADSC survival under oxidative stress. However, in the presence of bile acids, ADSC‐FXR exhibited a stronger antioxidative damage ability.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The bone marrow‐derived cell (BMDC) induces paracrine release of cytokines, exosomes, and growth factors to promote tissue regeneration and wound repair. [ 3 ] The therapeutic effects of BMDCs in diabetes‐related vascular complications, including DFUs, [ 4 ] diabetic nephropathy, [ 5 ] and limb ischemia, [ 6 ] have been reported. Although most of these studies focused on the beneficial BMDC‐induced paracrine factors, several studies have indicated that BMDCs from animals and individuals with diabetes evince a major beneficial‐to‐harmful alteration in their secretome components.…”
Section: Introductionmentioning
confidence: 99%